1997
DOI: 10.1111/j.1469-7610.1997.tb01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age of Entry, Day‐care Quality, and Family Characteristics on Preschool Behavior

Abstract: Teachers evaluated 155 4-5-year-old children attending Montréal day-care centers of excellent (N = 51), average (N = 60), or low (N = 44) quality using behavioral scales. Age of entry to day-care was also considered. Center quality was assessed by two observers using the Early Childhood Environment Rating Scale. Results point to the positive effects of longer exposure to high-quality group day-care (increased interest-participation), and the negative effects of longer exposure to low-quality centers (increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 38 publications
2
14
0
4
Order By: Relevance
“…Numerous studies have documented links between poor quality care and negative peer interactions (Clarke-Stewart, Gruber, & Fitzgerald, 1994;Howes, 1990;Howes, Smith, & Galinsky, 1995;Howes et al, 1996;NICHD ECCRN, 2001a) and externalizing behavior (Hausfather, Toharia, LaRoche, & Engelsmann, 1997;NICHD ECCRN, 1998;Votruba-Drzal, Coley, & Chase-Lansdale, 2004). Therefore, it is reasonable to expect that the quality of care would help account for the association between externalizing behavior and hours in child care.…”
Section: Five Causal Propositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have documented links between poor quality care and negative peer interactions (Clarke-Stewart, Gruber, & Fitzgerald, 1994;Howes, 1990;Howes, Smith, & Galinsky, 1995;Howes et al, 1996;NICHD ECCRN, 2001a) and externalizing behavior (Hausfather, Toharia, LaRoche, & Engelsmann, 1997;NICHD ECCRN, 1998;Votruba-Drzal, Coley, & Chase-Lansdale, 2004). Therefore, it is reasonable to expect that the quality of care would help account for the association between externalizing behavior and hours in child care.…”
Section: Five Causal Propositionsmentioning
confidence: 99%
“…Numerous studies have documented links between poor quality care and negative peer interactions (Clarke-Stewart, Gruber, & Fitzgerald, 1994;Howes, 1990;Howes, Smith, & Galinsky, 1995;Howes et al, 1996; NICHD ECCRN, 2001a) and externalizing behavior (Hausfather, Toharia, LaRoche, & Engelsmann, 1997; NICHD ECCRN, 1998;Votruba-Drzal, Coley, & Chase-Lansdale, 2004 Finally, to the extent that associations are found between externalizing behavior and a theoretically predicted process related to time in care, a causal effect of hours becomes more plausible. In this inquiry, therefore, we investigate the possibility that the process underlying the association between externalizing behavior and child care hours involves children spending many hours in environments in which children are abundant and adult attention is not.…”
Section: Five Causal Propositionsmentioning
confidence: 99%
“…Early age of entry to a lowquality child care facility was significantly correlated with anger-defiance behaviour, especially in boys or if there was parent or child stress. A high-quality child care centre negated this effect on anger-defiance and was beneficial to some children in the study, independent of the child's sex and the family structure (14). Other studies (15) have found that children who had attended a high-quality daycare within the first year of life had better school skills, fewer behaviour problems and had good peer social relationships.…”
Section: Behaviour and Developmental Outcomes Of Child Care Centresmentioning
confidence: 90%
“…Het bezoeken van een goed kinderdagverblijf, zo blijkt uit onderzoek, kan langdurige positieve effecten hebben op de sociale en persoonlijkheidsontwikkeling van kinderen, en op hun taalontwikkeling en schoolprestaties (Andersson, 1989(Andersson, , 1992Howes, 1990). Een onderzoek in Canada (Hausfather, Toharia, LaRoche & Engelsmann, 1997) illustreert heel mooi de beslissende rol die kwaliteit speelt in de vraag of kinderopvang positieve of negatieve effecten heeft. Hier werden excellente kindercentra vergeleken met kindercentra van lage kwaliteit.…”
Section: Risico-en Beschermende Factorenunclassified